Political Struggle of M. Fuad Köprülü: From Ruling Party to the Opposition (1956-1966) - Nasrullah Uzman (Gazi Akademik Bakış)
M. Fuad Köprülü who is known with his historian, thinker and the man of letters identity, is also a politician. He, who was the first Kars Parliamentarian of Republican People’s Party in 1935, was among the founders of Democratic Party in 1945. He served as a Minister of Foreign Affairs, minister of state and deputy prime minister between 1950-1956. He resigned from the Democratic Party in 1957, and couldn’t be a politician again, but he was still interested in active politics. He firstly supported The Freedom Party and then the Republican People’s Party. After the army’s confiscating to government on 27th May 1960, due to the events of 6th-7th September, he stood trial in Yassıada and was acquitted. He founded The New Democratic Party in 1961, but because of the fact that he couldn’t get the success he had expected, he had to withdraw from the active politics. In this article, M. Fuad Köprülü’s leaving the Democratic Party, his supporting the opposition party, his standing trial in Yassıada, foundation of the New Democratic Party and the political struggling after it, will be evaluated in the light of archival documents, newspapers of that period and other sources.